2013
DOI: 10.1002/jmri.24268
|View full text |Cite
|
Sign up to set email alerts
|

T2*-correction in dynamic contrast-enhanced MRI from double-echo acquisitions

Abstract: In DCE, a sufficiently short echo time should be used or corrections for T2*-effects based on double-echo acquisition should be made for correct quantification of kinetic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
(23 reference statements)
2
32
0
Order By: Relevance
“…This demonstrates that T 2 * correction of the muscle signal results in a substantial increase in the estimated AIF. A similar effect has been seen when T 2 * correction is applied directly to the plasma signal [6]. Figure 1f shows example model fits to the T 2 * corrected and uncorrected LTIC.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…This demonstrates that T 2 * correction of the muscle signal results in a substantial increase in the estimated AIF. A similar effect has been seen when T 2 * correction is applied directly to the plasma signal [6]. Figure 1f shows example model fits to the T 2 * corrected and uncorrected LTIC.…”
Section: Resultssupporting
confidence: 65%
“…The influence of T 2 * effect on lesion signal intensity and AIF can induce systematic errors in contrast kinetic parameter estimation as previous studies [6,17–20] showed. However, it has not been shown that T 2 * effect on contrast kinetic parameter estimation when a reference tissue approach is used where direct measurement of AIF is not feasible.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This approach has recently been shown to reduce errors in DCEderived parameters. 35 While this study suggests that DCE-and DSC-MRI data acquired by a multi-echo sequence may aid the diagnostics of N-status in rectal cancer patients, several potential study limitations needs to be addressed. First, the results must be interpreted in light of the limited sample size of this single center study.…”
Section: Grøvik Et Al: Dce-and Dsc-mri Of Rectal Cancermentioning
confidence: 91%